Antifungal effect of volatile organic compounds produced by Bacillus amyloliquefaciens CPA-8 against fruit pathogen decays of cherry. (June 2017) - Gotor-Vila, A.; Teixidó, N.; Di Francesco, A.; Usall, J.; Ugolini, L.; Torres, R.; Mari, M.
Abstract: The present work focuses on the antifungal effect of volatile organic compounds (VOCs) produced by Bacillus amyloliquefaciens CPA-8 against Monilinia laxa, M. fructicola and Botrytis cinera, three postharvest fruit pathogens of sweet cherry fruit. VOCs were evaluated with a double petri dish assay against mycelial and colony growth of target pathogens. For this purpose, CPA-8 was grown on different media and cultured for 24 and 48 h at 30 °C before assays. Data showed that mycelial growth inhibition was higher when CPA-8 was grown on Tryptone Soya Agar (TSA) while no differences were generally observed when CPA-8 was cultured for either, 24 and 48 h. Moreover, no effects were observed on colony growth. The main volatile compounds emitted by CPA-8 were identified by solid-phase microextraction (SPME)-gas chromatography as 1, 3 pentadiene, acetoin (3-hydroxy-2-butanone) and thiophene. Pure compounds were also tested in vitro on mycelial growth inhibition and their EC50 values against the three pathogens were estimated. Thiophene was the most effective VOC, showing more than 82% suppression of mycelial growth at the highest concentration (1.35 μL/mL headspace) and EC50 values ranging from 0.06 to 6.67 μL/mL headspace. Finally, the effectiveness of thiophene and CPA-8 VOCs was evaluated against artificially inoculated cherry fruits. Among the target pathogens, M. fructicola was clearly controlled by CPA-8 with less than 25% of rotten fruits compared to the control (65% disease incidence) and for all pathogens, less than 37.5% of CPA-8 treated decayed fruits produced spores (disease sporulation). Otherwise, pure thiophene showed no effect against any pathogen on disease incidence and disease sporulation. The results indicated that VOCs produced by B. amyloliquefaciens CPA-8 could develop an additive antifungal effect against postharvest fruit pathogens on stone fruit. Highlights: VOCs from CPA-8 were tested against mycelial and colony growth of M. laxa, M. fructicola and B. cinerea . Three different growth media were used for CPA-8 VOCs production. CPA-8 grown on TSA exhibited the highest percentage of mycelial growth inhibition. VOCs emitted by CPA-8 were identified by SPME-GC and selected for EC50 estimation. CPA-8 VOCs and pure thiophene were evaluated on artificially inoculated cherry fruit.